The Social Gospel Movement. An Overview - SIMUȚ, Ciprian (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2021)
The Social Gospel movement developed in a time of intense urbanization and in-dustrialization. The social context, generated by economic and political mishandlings, generated social pressure, poverty, and abuse, mainly on the poor and working classes. The Social Gospel movement tried to address the issues by applying Christian princi-ples to social structures, as a result of political and economic changes. The promoters of the movement aligned their view of the ideal society with the eschatological perspective of premillennialism. They argued that a society that eliminates social evil is the King-dom of God fulfilled. The movement managed to draw attention to social injustice, and it even managed to offer several productive means of alleviating the social evils it fought against. Despite its positive effects, the movement was criticized for failing to address is-sues such as race and gender. In this paper, the aim is to offer an introductory descrip-tion of the Social Gospel movement, as it was described in various critical writings.